Synthesis and degradation of poly-β-hydroxybutyrate in a sequencing batch biofilm reactor - Nogueira, R. (2009)
The aim of this work was the study of poly-β-hydroxybutyrate (PHB) formation and degradation in a sequencing batch biofilm reactor (SBBR). The SBBR was operated in cycles comprising three individual phases: mixed fill, aeration and draw. A synthetic substrate solution with acetate and ammonium was used. PHB was formed during the aeration phase immediately after acetate depletion, and was subsequently consumed for biomass growth, owing to the high oxygen concentration in the reactor. It was observed a combination of suspended and biofilm growth in the SBBR with predominance of the fixed form of biomass (506 Cmmol and 2102 Cmmol, respectively). Maximum PHB fraction of suspended biomass (0.13 Cmol/Cmol) was considerably higher than that of biofilm (0.01 Cmol/Cmol). This may possibly be explained by a combination of two factors: lower mass transfer limitation of acetate and higher fraction of heterotrophs in suspended biomass compared to the ones of biofilm.